Causes and Effects of Non-Rhoticity in Received Pronunciation: Implications for Saudi EFL Learners - Alghammas, Abdurrazzag (Forum for Linguistic Studies, 2025)
This study examines the phonological challenges posed by non-rhoticity in Received Pronunciation (RP) for Saudi learners of English as a Foreign Language (EFL), with a particular focus on how mother tongue interference and instructional limitations impact the perception and production of non-rhotic features such as linking /r/ and intrusive /r/. Drawing on a six-month qualitative investigation involving 100 Saudi secondary school students, the study employed longitudinal naturalistic observation to document recurring pronunciation patterns in real classroom contexts. The data were thematically analyzed using principles from applied phonology and second language acquisition research, revealing consistent misarticulations of RP-linked features, including difficulties with consonants such as /ð/, /θ/, /z/, and /k/. These pronunciation errors were primarily attributed to first language transfer from Arabic, insufficient exposure to authentic RP input, and a lack of explicit phonological instruction. The findings highlight a significant gap between learners’ exposure to English and their ability to reproduce RP features intelligibly. While RP continues to be valorized in academic and professional domains, it remains largely unfamiliar to learners without targeted phonetic training. The study argues for instructional reforms that integrate RP-based pronunciation into EFL curricula through focused pedagogical strategies, teacher training, and increased access to multimodal input. The research contributes to ongoing debates on English as an International Language (EIL), offering empirical insights into how socio-phonetic variation intersects with learner intelligibility in non-native contexts.